Distribution of Diplolaimella and Diplolaimelloides species from Patagonian lagoons and coastal waters (Nematoda: Monhysteridae), Chubut and Santa Cruz provinces (Argentina) - Pastor, Catalina Teresa (2009)
This paper focuses on Diplolaimella and Diplolaimelloides two very cosmopolitan genera inhabiting lotic freshwater to salty water inland, groundwater and coastal waters systems, providing a review of their taxonomy with new keys, and their distribution on the east coast of Patagonia and inland Patagonia. Two new species belonging to the genus Diplolaimelloides of the family Monhysteridae are described from Patagonian salty lagoons and coastal areas, and the Chubut and Santa Cruz provinces of Argentina: Diplolaimelloides tehuelchus sp. nov. has four bursal and three postcloacal papillae, short gubernaculum, and spicules longer than 50m; it has been found in Patagonian salty lagoons and in high coastal salt marsh areas. Diplolaimelloides warwicki sp. nov. is characterized by the angular shape of the spicules and the long gubernaculum. Diplolaimella ocellata is recorded for the first time in Patagonian salty lagoons and new localities in coastal waters are recorded for Diplolaimella gerlachi Pastor de Ward, 1984.